SIKAP BERBAHASA SISWA SEKOLAH DASAR DI KOTA SINGKAWANG: KAJIAN SOSIOLINGUISTIK - Ida Herawati (Balai Bahasa Kalimantan Barat, 2021)
The phenomenon of using language in educational institutions, especially elementary schools, attracted the attention of many sides because it was pointed out that several educational institutions use foreign or regional languages during learning and teaching process. The problem in this study is how the use of language and language attitudes of elementary school students in Singkawang. The aim of this study is to describe the use of language and language attitudes of elementary school students in Singkawang. The method used is descriptive with quantitative and qualitative approaches. Collecting data conducted by observation, interviews, and distributing questionnaires to several primary schools in Singkawang. The number of questionnaires distributed was 50 copies with details: respondent, the use of language, language attitudes, language activities, and attitudes towards neighboring countries. The analysis focus was related to language use and language attitudes. The analysis result showed that the use of Indonesian was more dominant than other languages, ranging between 28%-74%, local languages 24%-28%, and foreign languages 2%-28%. Elementary school students' language attitudes in Singkawang described the use of Indonesian 82.7% -96.2%, local languages 1.9% -13%, and foreign languages 1.9%-40.4%.